A comparison of Young's modulus for normal and diseased human eardrums at high strain rates. (2nd February 2009) - Luo, Huiyang; Lu, Hongbing; Dai, Chenkai; Gan, Rong Zhu
The viscoelastic properties of a human eardrum or tympanic membrane (TM) have not been fully characterised in the auditory frequency range, despite the fact that these properties are critical data as input in modelling the acoustic transmission in a human ear. In this paper using a miniature split Hopkinson tension bar (SHTB), we investigated the mechanical behaviour of TM at high strain rates, corresponding approximately to the behaviour at high frequency. The Young's modulus values of diseased human TMs are determined as 63.4-79.2 MPa in the radial direction, and 33.1-42.8 MPa in the circumferential direction at strain rates 300-2000 s−1, results are compared with those for normal TMs. The comparison indicates that normal human TMs show stronger dependence on high strain rates. The measured Young's modulus is converted into complex Young's modulus in the frequency domain in the frequency range of 300-2000 Hz.